DNA‐Origami‐Templated Growth of Multilamellar Lipid Assemblies. Issue 2 (9th November 2020) - Julin, Sofia; Nonappa; Shen, Boxuan; Linko, Veikko; Kostiainen, Mauri A.
Abstract: Lipids are important building blocks in cellular compartments, and therefore their self‐assembly into well‐defined hierarchical structures has gained increasing interest. Cationic lipids and unstructured DNA can co‐assemble into highly ordered structures (lipoplexes), but potential applications of lipoplexes are still limited. Using scaffolded DNA origami nanostructures could aid in resolving these drawbacks. Here, we have complexed DNA origami together with a cationic lipid 1, 2‐dioleoly‐3‐trimethylammonium‐propane (DOTAP) and studied their self‐assembly driven by electrostatic and hydrophobic interactions. The results suggest that the DNA origami function as templates for the growth of multilamellar lipid structures and that the DNA origami are embedded in the formed lipid matrix. Furthermore, the lipid encapsulation was found to significantly shield the DNA origami against nuclease digestion. The presented complexation strategy is suitable for a wide range of DNA‐based templates and could therefore find uses in construction of cell‐membrane‐associated components. Abstract : Modular DNA origami nanostructures can be used as nucleation sites for the growth of multilamellar lipid assemblies. The assembly process is driven by electrostatic and hydrophobic interactions and the DNA origami are encapsulated in the formed lipid matrix. The lipid encapsulation also remarkably protects the DNA origami against enzymatic digestion.